Pemetaan Tangkahan Pendaratan Ikan Berdasarkan Komoditas yang di Daratkan di Pulau Banyak, Aceh Singkil: Pemetaan Tangkahan Pendaratan Ikan Berdasarkan Komoditas yang di Daratkan di Pulau Banyak, Aceh Singkil - Rizal, Muhammad; Hamidi, Hamidi; Arif, Muhammad; Hafinuddin, Hafinuddin; Thahir, Muhammad Agam; Fuadi, Afdhal; Rahayu, Rosi (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2023)
Pulau Banyak and Pulau Banyak Barat Districts. play an active role in advancing capture fisheries production, this can be seen from the larger number and size of vessels operated so as to produce larger capture fisheries production. To land and sell their catch, many private entrepreneurs do it in their private holdings, not in government-owned fishing ports. This Tangkahan generally has relatively little land and facilities, but the activities and production are relatively large. This study aims to analyze the catch landed on the Tangkahans of Banyak Island, Aceh Singkil and make a map of the location of the Tangkahans in Pulau Banyak, Aceh Singkil. The method used is in 2 stages, the first stage is conducting a field survey using interview questionnaires, and the second stage is collecting field data (coordinate points of Tangkahan, types of catches and aerial photos of Tangkahan Island many). The location of the research is on Banyak Island, Aceh Singkil. The results of the study showed that there were 12 Tangkahans in Pulawa many, of which 8 units were in Baguk Village and 4 units were in Balai Desai. The catches that landed consisted of Squid, Dencis Fish, Tuna, Coral Anchovy and others. This is because the fishing gear used by Pulau Banyak fishermen is dominated by Bagan.